Immune system adaptations during competition period in female cross-country skiers - Stenholm, Johanna (2011)
Stenholm, Johanna. Immune system adaptations during competition period in female cross-country skiers. Master’s Thesis in Exercise Physiology, Department of Biology of Physical Activity. University of Jyväskylä. 95pp.